Предложение как основная синтаксическая единица в составе развитой письменной литературной речи - Драздаускас, А. (Kalbotyra, 1973)
The tenn “sentence” should be used only to denote the properly formatted syntactic units, and is therefore inapplicable to different kinds of casual utterances. The sentence is analysable in- to its “parts”. It is therefore futile to substitute other tenus for the latter or to try to do away with this concept altogether, which is especially harmful to proper linguistic education.The reality of the parts of the sentence is proved by applying different syntactic, semantic and phonetic (prosodic) criteria.